2003
DOI: 10.1002/ajmg.c.20015
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and bipolar disorder: New opportunities and challenges

Abstract: Despite significant effort, understanding of the molecular causes and mechanisms of bipolar disorder (BD) remains a major challenge. Numerous molecular genetic linkage and association studies have been conducted over the last two decades; however, the data are quite inconsistent or even controversial. This article develops an argument that molecular studies of BD would benefit significantly from adding an epigenetic (epiG) perspective. EpiG factors refer to modifications of DNA and chromatin that "orchestrate"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 100 publications
3
39
0
Order By: Relevance
“…5,12 Parent-of-origin effects imply an epigenetic mechanism of inheritance and may be a compelling hypothesis to explain complex genetic disorders such as bipolar disorder. [44][45][46] The paternal allele sharing in the Fallin et al 9 linkage study is described by microsatellite markers D18S59 and D18S63; the two loci (four SNPs) with putative parent-of-origin effects in this study map between these two markers and is therefore consistent with previous results. These loci confer substantial risk for bipolar disorder (fourfold and sixfold respectively, relative to maternal transmission).…”
Section: Discussionsupporting
confidence: 91%
“…5,12 Parent-of-origin effects imply an epigenetic mechanism of inheritance and may be a compelling hypothesis to explain complex genetic disorders such as bipolar disorder. [44][45][46] The paternal allele sharing in the Fallin et al 9 linkage study is described by microsatellite markers D18S59 and D18S63; the two loci (four SNPs) with putative parent-of-origin effects in this study map between these two markers and is therefore consistent with previous results. These loci confer substantial risk for bipolar disorder (fourfold and sixfold respectively, relative to maternal transmission).…”
Section: Discussionsupporting
confidence: 91%
“…49 Especially, POE in the transmission of bipolar disorder suggests the role of genomic imprinting. In bipolar disorder, several reports suggested the involvement of POE.…”
Section: Mitochondrial Dna (Mtdna) Heteroplasmymentioning
confidence: 99%
“…In humans, there is mounting evidence that epigenetic mechanisms are involved in the pathophysiology of stress-related disorders, including unipolar and bipolar depression (Mill and Petronis, 2007;Petronis, 2003). Postmortem studies of suicide victims with a history of depression or childhood abuse showed differential expression of DNMT subtypes (Poulter et al, 2008) and promoter-wide hypermethylation of ribosomal RNA gene promoters , respectively.…”
Section: Introductionmentioning
confidence: 99%